2004
DOI: 10.1158/0008-5472.can-03-2402
|View full text |Cite
|
Sign up to set email alerts
|

The Synthetic Triterpenoid 2-Cyano-3,12-dioxooleana-1,9-dien-28-oic Acid Induces Caspase-Dependent and -Independent Apoptosis in Acute Myelogenous Leukemia

Abstract: In acute myeloid leukemia (AML), resistance to chemotherapy is associated with defects in both the extrinsic and intrinsic pathways of apoptosis. Novel agents that activate endogenous apoptosis-inducing mechanisms directly may be potentially useful to overcome chemoresistance in AML. We examined the mechanisms of apoptosis induction by the novel synthetic triterpenoid 2-cyano-3,12-dioxooleana-1,9-dien-28-oic acid (CDDO) in AML cells. CDDO-induced apoptosis was associated with the loss of mitochondrial inner tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 44 publications
6
105
0
Order By: Relevance
“…1 cells is caspase mediated, but not totally caspase dependent. Consistent with these results, in acute myelogenous leukemia,CDDO has been found to induce both caspase-dependent and caspase-independent apoptosis [16].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…1 cells is caspase mediated, but not totally caspase dependent. Consistent with these results, in acute myelogenous leukemia,CDDO has been found to induce both caspase-dependent and caspase-independent apoptosis [16].…”
Section: Discussionsupporting
confidence: 61%
“…Studies have shown that CDDO-Im is more potent than its parent compound, CDDO, against murine melanoma and leukemic cells [7]. ST have been shown to provide effective control of cell growth of several tumor cell types [8] including breast cancer [9], lung cancer [10], ovarian cancer [11], melanoma [7], osteosarcoma [12], leukemia [13][14][15][16][17] and multiple myeloma cells [18,19]. Both CDDO and CDDO-Me are currently in Phase I clinical trials, with CDDO-Me being used in an oral form, highlighting the potential importance of these drugs as anti-cancer agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDDO induces apoptosis through both caspase-independent and -dependent mechanisms, the latter involving caspase-8 activation, Bid cleavage, cytochrome c release, and caspase-3 activation. [3][4][5][6] Furthermore, JNK, p38, and ERK pathways are involved in CDDO-induced apoptosis of tumor cell lines [7][8][9] mediated by disrupted intracellular redox balance and involving decreased glutathione and increased reactive oxygen species [9][10][11][12] CDDO-induced growth arrest of breast cancer cell lines correlates with transactivated PPARgamma and leads to up-regulation of p21 cip1waf1 , GADD153, CCAAT enhancer-binding proteins (CEBPs), and proteasome-regulatory factors, and to down-regulation of cyclin D1, PCNA, and IRS1. 13 CDDO and CDDO-Im activate the TGF␤ pathway through activation of Smad2/3, 14,15 which is required for the repression of inflammatory molecules by CDDO.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic OA derivatives modulated multiple signaling pathways and intracellular signaling molecules including NF-jB, AKT, STAT3, mTOR, caspases-3, -8, and -9, ICAM-1, VEGF, and PARP in a variety of cancer cells [14,[154][155][156]. In particular, synthetic OA derivatives induced apoptosis of acute myelogenous leukemia cells, upregulated c-Jun NH2 kinase mediated upregulation of DR5 in lung cancer cells and inhibited angiogenesis, invasion and metastasis of tumor cells [157][158][159]. The induction of phase-2 enzymes, such as hemeoxygenase 1 and NADPH-quinone oxidoreductase occurs by modulating Nrf2-Keap1 signaling pathway [160].…”
Section: Oleanolic Acidmentioning
confidence: 99%